Telaah Kritis terhadap Peran Hilah dan ‘Illah dalam Merespons Dinamika Pembentukan Hukum Islam - Zulaiha , Habibah; Rohman, Moh. Mujibur; Fatimah, Siti; Permatasari, Ermanita (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The study of ushul fiqh is a study that is often used to answer contemporary issues that are problems in life. The study of ushul fiqh is often used as an important thing in studying and formulating a law (istinbath al-hukm). A law will always develop according to its place and time because the nature of the law itself will not be separated from its dynamic nature. A law will change according to an 'illat. Where 'illat is very influential in forming a legal product. In addition to the problem of 'illat, the use of hilah as a method in seeking legal change by conducting legal hilah. This article is a study with a doctrinal type (library based) using library research to find data. Some of the data obtained were then analyzed with data reduction, data display and drawing. The results of the analysis state: 1) The problem of hilah is related to actions that result in the cessation of the obligations prescribed for mukallaf by carrying out an action that is basically permissible, but the action is prohibited because there is a certain intention. 2) The similarity of ‘illat is an important or key factor in the implementation or conflict of legal provisions that are manshus to ghairu manshus issues. On this basis, many new problems can be applied to the law using the reasoning of ‘illat.